The role of genetic diversity in the replication, pathogenicity and virulence of Murray Valley encephalitis virus - Niazi, Aziz-ur-Rahman (Curtin University, 2013)
Genetic and phenotypic variation of genotype 1 (G1) and genotype 2 (G2) Murray valley encephalitis virus (MVEV) were characterised. G2 viruses were a minority, had lower levels of genetic diversity and an attenuated phenotype in the mouse model of MVE. G1 isolates were abundant with higher levels of genetic diversity and a virulent phenotype. The restricted evolution of MVEV was due to multiplication in mosquito cells. An RT-qPCR assay detecting all MVEV genotypes was developed.